PENGARUH CASH HOLDING, PROFITABILITAS, DAN FINANCIAL LEVERAGE TERHADAP INCOME SMOOTHING PADA PERUSAHAAN MANUFAKTUR - Ibram Pinondang Dalimunte; Woni Prananti (EkoPreneur, 2019)
The objectives of this study are examine whether manufacture companies sector basic industry and chemicals that is listed in Indonesia Exchange over periode 2013-2017 do earning management with income smoothing through manipulating the amount of loan loss provisions along with influenced factors. Dependent variable used in this study is income smoothing, independent variables used in this study is cash holding, profitabilitas (net profit margin), and financial leverage (debt to equity ratio). This research used purposive sampling and kuantitatif, in determining sampel selection. A total of 22 companies sampel from 66 companies population. Eckel’s coefficient was used as a tool to indentify income smoothing. Subsequently performed descriptive statistics and logistic regression analysis to test each hypothesis by used eviews 7.0. The results of this study found that cash holding had no effect to income smoothing, profitability proxied by net profit margin and financial leverage proxied by debt to equity ratio had effect to income smoothing. and Simultaneously the cash holding, profitability, financial leverage had significantly effect to  income smoothing. Keywords: Income Smoothing, Cash Holding, Profitability, Financial Leverage. Keywords: Income Smoothing, Cash Holding, Profitability, Financial Leverage.